Interaction of Meloidogyne javanica and Macrophomina phaseoli in Kenaf Root Rot - Tu, C C (Journal of nematology, 1971)
Incidence and severity of root-rot caused by the fungus Macrophomina phaseoli was increased in screenhouse-grown kenaf (Hibiscus cannabinus L.) seedlings simultaneously infected by the nematode Meloidogyne javanica. In seedlings inoculated at 5, 10 and 15 days of age, root rot lesions increased 70.3, 44.1 and 21.8%, and nematode penetration increased 49.0, 36.7, and 12.3% when both fungus and nematode were present